Entre a (in)segurança urbana e a fragmentação socioespacial: as relações de sociabilidade em Ituiutaba-MG - Santos, Isabôhr Mizza Veloso dos (2020)
The impact of the processes of economic globalization, as well as the intensification of urbanization in the contemporary world, are correlated, breaking the ties that make up social cohesion in cities, transforming the daily lives of their inhabitants, marked by socio-spatial inequalities and urban violence. In this sense, we understand that to deal with the theme of urban violence is to understand its continuous appearances in cities, based on multiple hypervisibility mechanisms, often selective, that generally do not portray and face violence in its broadest sense. On the contrary, we find that the dominant representations of urban violence follow predefined scripts and discourses, which are similar in the most different cities. Daily practices are selective, privileging private spaces over public ones, in which it is expected to have effective possibilities to control sociability relations. Such aspects reinforce the process of socio-spatial fragmentation that advances through urban restructuring, based on the production of the urban fabric and the realization of daily securitization practices, together with the imaginary about cities and their different city dwellers. Thus, with regard to the general objective of the study, we seek to analyze the relationship between urban (in) security and socio-spatial fragmentation, based on the understanding of the objective and subjective dynamics that permeate the spatial practices of the citizens of Ituiutaba, in the mining triangle. This is because we believe that activities associated with violence and urban (in) security and their symbolic representations directly influence the appropriation of the city, promoting avoidance and stigmatization of neighborhoods and their citizens, which contributes to breaking the cohesion of urban life, contributing to the process of socio-spatial fragmentation. In this sense, these processes are analyzed from the city of Ituiutaba-MG, inserted in a non-metropolitan context, aiming to highlight the specificities of an urban context considered as safer when compared to metropolises and large cities. In the methodological scope, we used a set of quantitative and qualitative information to understand the process of socio-spatial fragmentation in Ituiutaba in terms of urban daily life and from the perspective of urban insecurity: a) rates of total criminal occurrences and distributed by neighborhoods; b) semi-structured interviews with different city profiles and c) fieldwork in the city's neighborhoods. Thus, the reflections made were based mainly on the social representations of city dwellers, on their opinions and on the descriptions of their daily practices, in order to better understand the local experience as opposed to the data referring to urban violence. We found with the research that in Ituiutaba the imaginary of urban insecurity influences the consolidation of the tendency of socio-spatial fragmentation, due to a more privatist, individualistic and separatist experience, affecting the sociability relations between the Ituiutaban citizens and fostering barriers to the Right to the City.